VO2-based switchable transmit-reflect-array for THz applications - Qureshi, Suhail Asghar; Kamarudin, Muhammad Ramlee; Abbasi, Muhammad Inam; Abidin, Zuhairiah Zainal; Dahri, Muhammad Hashim; Ashyap, Adel Yahya Isa; Ramli, Nordin (2023)
This work presents the design of a unit cell of Transmit-Reflect-Array with two independent operations in the THz band. The size of a unit cell is 0.136 mm, which is composed of six layers in total. The mode of operation completely relies on the states of graphene and VO2 materials. The performance of reflectarray is analyzed when both VO2 and graphene act as metallic layers. Nearly 360° phase shift in reflectarray operation was obtained regardless of the dimensions of transmitarray and more than 400° phase shift was obtained in transmission mode with the negligible effect of reflection patch element length. The proposed method can be used for manipulating the characteristics of the reflecting or transmitting beam independently for bidirectional THz communication applications.